(untitled) (ENTHYMEMA, 2023)
In the face of the theories that dismiss digital arts for being facilitated by the capitalist system, this paper argues that a critical awareness on the dangers of new technologies does not necessarily lead to the condemnation of technological arts. Indeed, the evidence suggests that digital technologies are an excellent medium through which literature can voice a nuanced and critical consideration about the world in which it appears. The analysis focuses on Spanish-Argentinian writer Belén Gache’s transmedia project Kublai Moon (2013-2019) in order to demonstrate that hypothesis. Firstly, it is shown that the novel reflects on the compatibility between humans and machine, in its content as well as in its forms. Secondly, it is contended that the axiological judgments on literature must be based on updated criteria when it comes to evaluating digital works.